Endovascular Repair of Saccular Ascending Aortic Aneurysm After Orthotopic Heart Transplantation Using an Investigational Zenith Ascend Stent-Graft. (August 2015) - Oderich, Gustavo S.; Pochettino, Alberto; Mendes, Bernardo C.; Roeder, Blayne; Pulido, Juan; Gloviczki, Peter
Purpose: To report the use of an investigational stent-graft to treat an ascending aortic aneurysm in a patient with a heart transplant.Case Report: A 48-year-old man presented with a 3.5×1.5-cm saccular aneurysm in the mid anterior ascending aorta, abutting the sternum. The patient's history was notable for placement of a left ventricular assist device followed by orthotopic heart transplantation 2 years prior to treat end-stage familial dilated cardiomyopathy. Under compassionate use, a custom-designed ascending aortic stent-graft (Zenith Ascend) was successfully delivered via an 18-F system and deployed just distal to the origin of the left main coronary artery under pulmonary artery catheter–guided rapid ventricular pacing. The patient was discharged the next day, and 6-month follow-up was unremarkable. Imaging at 5 months showed an excluded aneurysm sac with no endoleak or migration.Conclusion: The ideal ascending aortic stent-graft should be low profile, conformable to the arch anatomy, with short tip delivery system and a stepwise deployment mechanism that allows precise placement relative to the ostia of the coronary arteries and the innominate artery. This case illustrates the advancement of endovascular techniques to the most challenging segment of the aorta to decrease morbidity and mortality in high-risk patients.